Osteonecrose medicamentosa, osteomielite e osteorradionecrose: estudo imunoistoquimico comparativo - De Antoni, Carlos Cesar (2018)
Bisphosphonate-related osteonecrosis of the jaws (BRONJ), osteomyelitis (OM) and osteoradionecrosis (ORN) present a great deal of similarity in clinical and radiographic aspects. In order to investigate the microscopic aspects of each disease, and with few comparative studies, especially immunohistochemical analyzes, the objective of this study was to compare the immunoexpression of markers related to the rhythm of bone remodeling and vascularization among the three diseases. Patients were selected from patients who underwent previous biopsy with the diagnosis of the three diseases: OM, BRONJ and ORN. The slides of each specimen were subjected to immunoblots using the OPG, RANKL, VEGF and CD31 antibodies. Blind semiquantitative analysis was performed by an examiner, and was checked by a supervisor. The sample obtained was 34 specimens from 34 patients, 16 patients with BRONJ, 6 with chronic OM and 12 with ORN. Considering the value of p <0.05, no significant difference in the expression of the markers between the diseases was identified. Through this study, it can be affirmed that considering the markers related to the rhythm of bone remodeling and vascularization, the analyzed diseases were not differentiated.